2002
DOI: 10.1038/sj.sc.3101324
|View full text |Cite
|
Sign up to set email alerts
|

Neurological outcome following laminectomy in spinal metastases

Abstract: Study design: Retrospective outcome measurement study. Objectives: Patients suering from malignant tumour disease and metastases to the spine develop a variety of clinical complaints including radicular symptoms and/or spinal cord compression syndromes. Palliative decompressive laminectomy with total or partial tumour resection is an acknowledged method of treatment, despite controversy. Setting: The Department of Neurosurgery of the University of Vienna. Method: Patients suering from metastases with predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 20 publications
1
15
0
2
Order By: Relevance
“…1,12,23,45 Two studies reported outcomes after decompression without stabilization. Schoeggl et al 39 reported results of decompressive laminectomy with total or partial tumor removal. The authors found that patients undergoing this technique experienced an improvement in their quality of life based on a reduction in analgesic consumption postoperatively and a decrease in the total percentage of patients experiencing continence disorders following surgery (Table 3).…”
Section: Description Of Surgical Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…1,12,23,45 Two studies reported outcomes after decompression without stabilization. Schoeggl et al 39 reported results of decompressive laminectomy with total or partial tumor removal. The authors found that patients undergoing this technique experienced an improvement in their quality of life based on a reduction in analgesic consumption postoperatively and a decrease in the total percentage of patients experiencing continence disorders following surgery (Table 3).…”
Section: Description Of Surgical Techniquesmentioning
confidence: 99%
“…The techniques reported on were posterior decompression and stabilization, posterior decompression without stabilization, and posterior decompression with total or subtotal tumor resection. 1,12,23,39,45 The outcomes measures used to compare surgical technique varied across the 7 included studies. Four studies used the American Spinal Injury Association (ASIA) Impairment Scale to assess neurological function.…”
Section: Description Of Surgical Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the evidence, however, this procedure continues to be performed by some surgeons. 74 The results of decompressive laminectomy seem to be improved if internal fixation (for example, pedicle screws) and fusion are performed as well. In a review of 134 patients treated with either a laminectomy (111 patients) or laminectomy with stabilization (23 patients), Sherman and Waddell, 75 found that the latter group had better posttreatment ambulatory status (92 compared with 57%), sphincter function, and pain control, and less recurrent neurological dysfunction.…”
Section: Neurosurg Focus / Volume 15 / November 2003mentioning
confidence: 99%